TEKNIK INVESTIASI PADA KECELAKAAN KERJA - Arvina Putri Utami (CV. Adiba Aisha Amira, 2023)
The number of work accidents in Indonesia in the Southeast Asia region is the second highest. The high number of work accidents is one of the problems that occur in workers and employers. This work accident usually occurs due to factors from the worker himself or the work environment which in this case is the employer's side. In principle, all potential work accidents need to be prevented, one of which is by conducting an investigation. The purpose of this research is to find out the investigative techniques on work accidents. The method used is the Literature Review method (literature study). The research results obtained were physical examination, requesting information and confirmation, checking documents, analytical review, recalculating, (reperforming), net worth method and follow the money. While the findings of the literature review obtained in the first article are the basic causes of accidents from individual factors, work factors and management factors. In the findings of the second article, it was found that the causes of work accidents were a lack of knowledge, attitudes, availability, and supervision of PPE, there was still a lack of awareness from the workforce regarding the responsibilities for using PPE according to the type of work and the risks of the hazards posed. And the findings of the third article found that the cause of work incidents is a lack of attention to safety aspects, for example working at a speed that exceeds the normal limit followed by a careless attitude, printing is synonymous with the use of chemicals in the work process. Therefore, this potential chemical hazard can enter or aflect the body of the workforce.